2018
DOI: 10.7717/peerj.6104
|View full text |Cite
|
Sign up to set email alerts
|

Early swelling response to phytohemagglutinin is lower in older toads

Abstract: The effects of age on performance of life-history traits are diverse, but a common outcome is senescence, an irreversible deterioration of physical and physiological capabilities of older individuals. Immune response is potentially bound to senescence. However, little is known about immune response ageing in amphibians. In this work, we test the hypothesis that amphibian early immune response is reduced in older individuals. To this end, we captured adult natterjack toads (Epidalea calamita) and inoculated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 89 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…2011 ). In fact, senescence often implies a deterioration of the immune system ( Zamora-Camacho and Comas 2018 ), which also leads to higher mortality due to pathogens and parasites. However, senescence is strongly determined by telomere length ( Haussmann and Marchetto 2010 ) and, in our study population, telomeres lengthen up to 4 years old, and then shorten ( Burraco et al.…”
Section: Discussionmentioning
confidence: 99%
“…2011 ). In fact, senescence often implies a deterioration of the immune system ( Zamora-Camacho and Comas 2018 ), which also leads to higher mortality due to pathogens and parasites. However, senescence is strongly determined by telomere length ( Haussmann and Marchetto 2010 ) and, in our study population, telomeres lengthen up to 4 years old, and then shorten ( Burraco et al.…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies have directly compared age and swelling responses from PHA, while two others compared development time and PHA response ( Abu Bakar et al , 2016 ; Zamora-Camacho and Comas, 2018 ). Abu Bakar et al (2016) found that PHA-induced oedema in Litoria aurea exposed to Bd was higher in adults than in either subadults or juveniles.…”
Section: Analysis Of Existing Amphibian Pha Studiesmentioning
confidence: 99%
“…In general, larval immune systems are less developed and robust than adult immune systems, and aspects of the immune system are suppressed during metamorphosis in anurans, although much less is known about urodeles ( Rollins-Smith, 1998 ; Abu Bakar et al , 2016 ; Grogan et al , 2018 ). Another study on Epidalea calamita performed on adults exclusively found that swelling decreased with age, leading study authors to suggest that senescence may reduce immunocompetence after reaching adulthood ( Zamora-Camacho and Comas, 2018 ). Two studies looking at the relationship between development time and immunocompetence found that increased development time in response to stress is associated with reduced PHA response ( Gervasi and Foufopoulos, 2008 ; Seiter, 2009 ).…”
Section: Analysis Of Existing Amphibian Pha Studiesmentioning
confidence: 99%
See 2 more Smart Citations